Burden and pattern of diseases among tribes of South-West Rajasthan - Rakhi Dwivedi; Prachi Goel; Riddhi Jain; Aditya Sharma; Pradeep Dwivedi; Pratibha Singh; Kuldeep Singh (Journal of Family Medicine and Primary Care)
Introduction: Policymakers can better grasp regional health challenges by investigating the disease profile in a specific area. It is challenging to understand the burden and pattern of diseases in the aspirational district of Sirohi, Rajasthan, which is also a partially tribal district, due to the lack of studies on disease profiling among the tribals in the state. Aim: To determine the prevalent diseases among the people of district Sirohi through secondary data analysis of data collected from government healthcare facilities. Materials and Methods: We conducted a retrospective analysis of health data from the records of the government health system in the district Sirohi, Rajasthan, for the last three years, from 2020 to 2022. Our analysis specifically examined illnesses that affected pregnant women, children, and patients attending outpatient and inpatient departments. Results: Over three consecutive years, tribal blocks had a higher load of diseases compared to the non-tribal blocks of the Sirohi district. Diarrhoea contributed 67.9% of childhood illnesses, followed by pneumonia (14.4%). The occurrence of maternal anaemia among pregnant women was 81%, with a noticeable upward trajectory. The most common reasons for admission to the in-patient department were respiratory illnesses (n = 6,145), diarrhea with dehydration (n = 4,339), snake bites (n = 687), and typhoid (n = 539). Pindwara had the highest number of respiratory illness (n = 2897, 47.1%) compared to all other blocks. Conclusion: This study emphasizes the necessity of addressing the health challenges encountered by tribes in district Sirohi. To tackle these issues, it is imperative to execute a targeted and precise strategy. There is a lack of data within tribal communities, which necessitates additional research to formulate a targeted strategy for tribal health.